Great events from history. - Lewis, Thomas T. (Thomas Tandy) (Great events from history., 2017)
Salem Press' monumental Great Events from History series spans human history from ancient times to the present, worldwide. This new three-volume set continues Salem's award-winning coverage into the twenty-first century, providing thoughtful, detailed essays on major events between 2000 and 2016. The first sixteen years of the twenty-first century have seen tumultuous and life-changing events- terror, wars, natural disasters, as well as social and political events that will render the world forever changed. This text documents it all-the 9/11 attack on the Twin Towers, the wars in Afghanistan and Iraq, natural disasters around the globe, the election of the first African-American President. Plus, important social and cultural developments, including the rise of digital and social media, as well as breakthroughs in science and medicine.